EVALUATION OF SHELF LIFE OF SACHET WATER PRODUCED IN JOS NORTH, PLATEAU STATE - Ezekiel, OIGANJI; Emmanuel, Zakka Junior; Bello, Ezra (FUDMA Journal of Sciences, 2020)
Sachet water has gradually become the most widely consumed portable water for everyone in Nigeria. This study aimed to assess physiochemical and bacteriological properties of selected sachet water brands. Random sampling method was used to collect data from 20 selected brands within Jos North Metropolis, the 20 selected brands served as sampling frame where by 3 brands were selected for the pilot study. The three brands selected as pilot study were; FEDCOF, LOANE and MCEDEN. The samples of sachet water were collected from the 3 different brands within 24 hours of production which were transported to Bauchi State Water Board for analysis. The parameters were analyzed following standard procedures to determine the physical chemical and bacteriological content of the samples. The physiochemical properties of the samples were analyzed, it was observed that  the following parameters: pH, Temperature, Turbidity, Total Dissolve Solid, Total Hardness, Conductivity, Alkalinity, Nitrate, Sulphate, Chloride and Iron were within the permissible limit, as compared to National Agency for Food and Drug, Administration Control  and Standard Organization of Nigeria standards. Furthermore, bacteriological analysis was carried out on the three brands of sachet, remarkable presence of Faecal coli form count and total coliform count were detected and were though above the permissible limit set by NAFDAC and SON. It can be concluded that FEDCOF, LOANE and MCEDEN brands of Sachet in Jos North should not be consumed, when it has been kept beyond six (6) weeks, if consumed it may cause illnesses like typhoid fever, hepatitis, gastroenteritis and dysentery.
Keywords: Shelf life, bacteriological, physiochemical, sachet, water.